Psychotherapy effectiveness for major depression: a randomized trial in a Finnish community. Issue 1 (December 2016) - Saloheimo, Hannu; Markowitz, John; Saloheimo, Tuija; Laitinen, Jarmo; Sundell, Jari; Huttunen, Matti; A. Aro, Timo; Mikkonen, Tuitu; O. Katila, Heikki
Abstract Background The purpose of this study is to assess the relative effectiveness of Interpersonal Psychotherapy (IPT), Psychoeducative Group Therapy (PeGT), and treatment as usual (TAU) for patients with Major Depressive Disorder (MDD) in municipal psychiatric secondary care in one Finnish region. Methods All adult patients (N = 1515) with MDD symptoms referred to secondary care in 2004-2006 were screened. Eligible, consenting patients were assigned randomly to 10-week IPT (N = 46), PeGT (N = 42), or TAU (N = 46) treatment arms. Antidepressant pharmacotherapy among study participants was evaluated. The Hamilton Depression Rating scale (HAM-D) was the primary outcome measure. Assessment occurred at 1, 5, 3, 6, and 12 months. Actual amount of therapists' labor was also evaluated. All statistical analyses were performed with R software. Results All three treatment cells showed marked improvement at 12-month follow-up. At 3 months, 42 % in IPT, 61 % in PeGT, and 42 % in TAU showed a mean ≥50 % in HAM-D improvement; after 12 months, these values were 61 %, 76 %, and 68 %. Concomitant medication and limited sample size minimized between-treatment differences. Statistically significant differences emerged only between PeGT and TAU favoring PeGT. Secondary outcome measures (CGI-s and SOFAS) showed parallel results. Conclusion All three treatments notably benefited highly comorbid MDD patients in a public sector secondary care unit. Trial registration ClinicalTrials.govNCT02314767 (09.12.2014).